Assessing the Role of School Leadership in Mediating the Impact of Teacher Professional Development on Curriculum Implementation in Indonesia - Judijanto, Loso; Suwarna, A. Idun; Hanim, Siti Aisyah; Nuswantoro, Patriandi; Noviyani, Rafiqa (The Eastasouth Journal of Learning and Educations, 2024)
This study examines the mediating role of school leadership in the relationship between teacher professional development (TPD) and curriculum implementation in Indonesian schools. Using a quantitative approach, data were collected from 160 teachers across various regions, utilizing a Likert-scale questionnaire to measure perceptions of TPD, leadership practices, and curriculum implementation effectiveness. Structural Equation Modeling with Partial Least Squares (SEM-PLS) was applied to test the hypothesized relationships. The findings indicate that school leadership has a significant direct impact on curriculum implementation and an indirect effect through its influence on TPD. School leadership was shown to enhance TPD outcomes, which in turn positively affected curriculum implementation, highlighting the importance of an integrated approach where leadership and TPD efforts are aligned to drive successful curriculum outcomes. These results have practical implications, suggesting that investment in leadership training and needs-based TPD can strengthen curriculum application, contributing to improved educational quality.